The Perception of Coastal Communities toward the Relationship of Social-Entrepreneurship, Socio-Economic and Quality of Life - Wan Abd Aziz, Wan Mohd Amin; Muhd. Abi Sofian, Abdul Halim; Mohd Shaladdin, Muda (Mediterranean Centre of Social and Educational Research, 2015)
This study presents an insight perception of coastal entrepreneurs with regards to the business opportunities that have been accommodated by government to increase their level of income, employment opportunity and quality of life. The aim of the study is to identify the factors of social-entrepreneurship in developing the socio-economic as well as to change the coastal communities’ social life in Terengganu. Simple random sampling was used to distribute 300 questionnaires among coastal entrepreneurs in east coast Malaysia. However, there are only 266 set of questionnaires were replied. The results indicate that factors of cooperation, non-profit and welfare in social-entrepreneurship are contributed to the quality of life. Meanwhile, the factor of socio-economic becomes important mediator in association of welfare and quality of life. In summary, the study will help the state governments in east-coast Malaysia to identify the factors and items that important to coastal entrepreneurs in developing their business performance as well as contributing to the changing of their social-life.